E-Learning: A Veritable Tool to Step-Up Accessibility in the Nigerian Educational Sector - Archibong, Florence Imaobong; Ugwulashi, Chima Sabastine (Mediterranean Journal of Social Sciences, 2012)
This paper addresses E-learning as a veritable tool to step up accessibility in the Nigerian educationalsector highlighting the concepts of ICT as a tool for improving educational process, access and availabilityof ICT resources in Nigeria secondary schools, e-learning technologies and sustainable development aswell as e-learning/online learning/distance learning. Also, challenges to e-learning in the Nigerian highereducation sector and benefits of e-learning in the Nigerian educational system were treated. Since eeducationfacilitates teaching and learning, it is therefore suggested that a comprehensive feasibility studybe adopted by all stakeholders, there should be mass computer literacy programmes, government shouldensure the growth of ICT from primary to tertiary institution, and the ICT teachers should be motivatedthrough incentives to enhance job satisfaction.